High-efficiency, stable and non-chemically doped graphene–Si solar cells through interface engineering and PMMA antireflection. Issue 12 (26th January 2016) - Jiao, Tianpeng; Wei, Dapeng; Song, Xuefen; Sun, Tai; Yang, Jun; Yu, Leyong; Feng, Yanhui; Sun, Wentao; Wei, Wei; Shi, Haofei; Hu, Chenguo; Du, Chunlei
Abstract : High-efficiency and stable graphene–Si heterojunction solar cells without chemical doping were achieved through introducing a thin passivation layer of carbon nanowalls and an antireflection film of PMMA to increase light absorption. Abstract : In graphene–Si (Gr–Si) solar cells, chemical doping could remarkably enhance the performance of the cells, but weakens their stability, which limits their further application. However, in terms of the efficiency of pristine cells, the interfacial defect states and the increased thickness of the oxide layer in air also make high-efficiency and stable cells more difficult to achieve. Here we directly grew carbon nanowalls (CNWs) as a passivation layer onto the Si surface, which could obviously increase the efficiency. On the other hand, a poly(methyl-methacrylate) (PMMA) film was retained after transferring graphene, which could not only keep the graphene intact, but could also serve as an efficient antireflection layer for greater light absorption of the Si. A maximum PCE of 8.9% was achieved for a PMMA-bilayer Gr-CNWs-Si solar cell. Our cell's efficiency showed a slight degradation after being stored in air for 4 months. This result is far superior to other previously reported stability data for chemically doped Gr–Si solar cells. The PMMA-Gr-CNWs-Si solar cell, with high efficiency and stability, possesses important potential for practical photovoltaic applications.